2020
DOI: 10.1542/peds.2020-0375
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Health Outcomes Following In Utero Exposure to Influenza Vaccines: A Systematic Review

Abstract: CONTEXT: Vaccination during pregnancy is an effective strategy for preventing infant disease; however, little is known about early childhood health after maternal vaccination. OBJECTIVES: To systematically review the literature on early childhood health associated with exposure to influenza vaccines in utero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
(103 reference statements)
0
15
0
Order By: Relevance
“…The World Health Organization (WHO) and the United States of America Centers for Disease Control and prevention (CDC) recommend use of maternal tetanus vaccine, Influenza vaccine, and Tdap vaccine, to provide protection of infants through protective maternal antibodies [7][8][9]. Evidence exists to show the maternal immunization effectiveness [10,11] and safety [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) and the United States of America Centers for Disease Control and prevention (CDC) recommend use of maternal tetanus vaccine, Influenza vaccine, and Tdap vaccine, to provide protection of infants through protective maternal antibodies [7][8][9]. Evidence exists to show the maternal immunization effectiveness [10,11] and safety [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although there were singular findings of increased risk of asthma, sepsis, Sjögren syndrome, and autism, none were significant after accounting for multiplicity of outcomes assessed. 47 We observed a small inverse association between Tdap vaccination during pregnancy and rates of upper and lower respiratory infections. In a case-control study, Sukumaran et al 46 observed a lower odds of maternal Tdap vaccination among infants with a respiratory-related 2.3 (0.0-6.0) 3.5 (0.0-6.0) -2.3 (0.0-6.0) 2.5 (0.0-6.0) -…”
Section: Figurementioning
confidence: 59%
“…In a recent systematic review, just 9 such studies were identified, the majority of which were conducted to assess early childhood outcomes after prenatal vaccination with 2009 influenza A virus subtype H1N1 (A/H1N1) pandemic monovalent influenza vaccines. 47 No meta-analysis was possible owing to variability in outcomes assessed; 2 studies recorded risk reductions for upper respiratory tract infection, allcause hospitalization, and gastrointestinal infection in offspring exposed to maternal 2009 A/H1N1 pandemic influenza vaccination. Although there were singular findings of increased risk of asthma, sepsis, Sjögren syndrome, and autism, none were significant after accounting for multiplicity of outcomes assessed.…”
Section: Figurementioning
confidence: 99%
“…Overall, 16 systematic reviews on adverse events following vaccination with monovalent H1N1pdm09 vaccines were included. According to the AMSTAR 2 assessment tool, five of the systematic reviews were considered high quality (20)(21)(22)(23)25), two were considered low quality (31,33). The rest were considered moderate quality.…”
Section: Discussionmentioning
confidence: 99%
“…A narrative systematic review by Foo et al (23) was the only review concerning long-term effects of H1N1pdm09 vaccination during pregnancy on early childhood health outcomes. The review identified six primary studies which assessed the effect on influenza infections, primary infections only, childhood mortality up to the age of 5, and two registry studies assessing the effect on infections, hospitalisations, and general diseases and syndromes.…”
Section: Long Term Effects In Children Following Maternal H1n1pdm09 Vaccinationmentioning
confidence: 99%